2016
DOI: 10.1080/13880209.2016.1216130
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal screening of the Cuban native plant Scutellaria havanensis

Abstract: Context: Scutellaria havanensis Jacq. (Lamiaceae) is a native medicinal herb with a history of use in Cuba.Objective: This study screens the antiprotozoal activity of S. havanensis. Materials and methods: Chloroform and methanol extracts from leaves and stems were evaluated in vitro at doses between 0.015 and 200 lg/mL against protozoan parasites: Plasmodium berghei, Trichomonas vaginalis and Leishmania amazonensis. Chloroform and methanol extracts were characterized by GC/MS. Cytotoxicity against mouse perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…El grado de toxicidad del extracto se definió en fun-ción del rango en que se encontró el valor de CL50 de acuerdo con las categorías siguientes: extremadamente tóxico (CL50< 10 µg/mL), muy tóxico (10< CL50 <100), moderadamente tóxico (100< CL50 <1 000) y no tóxico (CL50> 1 000 µg/mL). 23 Por lo tanto, el extracto polar de B. variegata se considera no tóxico.…”
Section: Cepaunclassified
“…El grado de toxicidad del extracto se definió en fun-ción del rango en que se encontró el valor de CL50 de acuerdo con las categorías siguientes: extremadamente tóxico (CL50< 10 µg/mL), muy tóxico (10< CL50 <100), moderadamente tóxico (100< CL50 <1 000) y no tóxico (CL50> 1 000 µg/mL). 23 Por lo tanto, el extracto polar de B. variegata se considera no tóxico.…”
Section: Cepaunclassified
“…The methanol and chloroform extracts of S. havanensis leaves and stems contain high concentrations of flavonoids including bioactive wogonin. Wogonin in the chloroform extract indicated its specific anti-plasmodial effect with respect to mammalian cells and thus could be useful for the development of antimalarial alternatives [25]. These compounds are synthesized in glandular trichomes that serve the function of defense and source of valuable chemicals and are also used as taxonomic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Fernández-Calienes Valdés, Monzote Fidalgo [ 32 ] found that extracts of leaves and stems of Scutellaria havanensis , a plant native to Cuba, and the isolated flavonoid compound wogonin (Fig. 2 ) exhibited anti-trichomonad activity against T. vaginalis with the following selectivity indices: methanol extract 7.3; chloroform extract 2.8; wogonin 2.0; and metronidazole 322.6.…”
Section: Introductionmentioning
confidence: 99%